Structure, content and direction of physical preparation of elite ice hockey players in the annual training macrocycle - Rotenberg, R. B. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to develop a model for the physical training process of high-level hockey players within a year-long training macrocycle, taking into account the dynamics of the ratio of general and special physical training at different stages of the sports season. Methods and structure of the study. The empirical basis of the study consisted of training plans, schedules, and working materials from the SKA hockey club's training system. The structure and content of training programmes at various stages of the annual macrocycle were analysed. To assess the dynamics of physical fitness, the study focused on general and specific endurance as key qualities that directly affect game performance. Monitoring was carried out using instrumental tests conducted both on and off the ice. The choice of these tests was determined not only by their sensitivity to changes in the athlete's functional state, but also by their practical orientation – they allow us to judge the player's ability to perform technical and tactical actions at a high level of intensity, which is fundamentally more important than, for example, abstract indicators of lower limb muscle strength. We are not so much interested in ‘how strong the legs are’ as in whether the attacker can run away from the defender and the defender can catch up with the attacker – and in this sense, ‘pure’ running on the court and specific endurance tests better reflect the actual playing form. Results and conclusions. An analysis of specialised sources has shown that a hockey player's ability to maintain a high pace of play throughout the match can be considered a key criterion of special endurance. Hockey is characterised by high intensity and the involvement of large muscle groups, which leads to significant energy expenditure. In this context, special endurance can be considered an integral indicator reflecting the player's level of functional readiness. At the same time, it should be emphasised that the study of this indicator does not exclude the importance of other components of physical fitness, but in the conditions of high competitive load of professional hockey, it is necessary to use optimised and applied monitoring methods. It has been established that indicators of general endurance, which are closely related to the aerobic capacity of the body, tend to decrease during long tournament cycles, especially when there are a large number of away games. This can have an impact on the reduction in the speed of recovery and the overall level of adaptation of players. At the same time, it was found that general endurance indicators do not show statistically significant differences depending on the players' positions and skill levels. At the same time, specific endurance indicators vary depending on the player's position and show a significant increase with the improvement of the hockey players' athletic skills, which confirms their high sensitivity and practical significance in the process of assessing functional status and planning training impact.